Analisis Manajemen Pengelolaan Obat di Gudang Farmasi Rumah Sakit X - Maulidi Arkan, Ulfa; Marian Tonis; Abdul Zaky (LPPM, Universitas Muhammadiyah Riau, 2023)
Drug management is one of the most important parts of hospital management in the provision of health services as a whole, because inefficiency and inefficiency in management will have a negative impact on the hospital both from a medical, social and economic perspective. Based on the results of the document review, there are expired drugs in the Pharmacy Installation in 2021 where there are 4,454 expired drugs in the Pharmaceutical Warehouse, the Emergency Room and Inpatient Pharmacy Depots have 1,173 Expired Drugs and the Outpatient Pharmacy Depot has 2,180 expired drugs. Expired drugs in 2022 where there are 37,959 expired drugs in the Pharmaceutical Warehouse, , ER and Inpatient Pharmacy Depots have 6,582 expired drugs and Outpatient Pharmacy Depots have 31,852 expired drugs. The purpose of this study is to determine the Management of Drug Management in the Pharmacy Warehouse of the X Hospital. This study uses a type of qualitative research with a descriptive observation approach, with a total of 4 informants. This research was conducted using in-depth interviews, observation and document review methods. The results of the study found that drug planning uses the consumption method which is carried out every two months, the determination of the types of drugs in the procurement is adjusted to the National Formulary and is constrained by distributor receivables, the receiving process sometimes the goods that arrive do not match the invoice, and the storage is not up to standard, there is no Special room for expired drugs. It is recommended that the planning process use a combination of consumption and epidemiology methods so that empty drugs and over stock do not occur, the need for a special place for storing expired drugs, and expanding storage warehouses so that there is no more cardboard buildup.